Effect of probiotic encapsulated Artemia Nauplii on the digestive enzyme activity in post larvae of Penaeus Monodon - S. JYOTHSNA,; D. SAI VINATHI,; V. KALARANI, (International Journal of Pharma and Bio Sciences, 2018)
Though Global shrimp production and trading had significantly increased in the past 20 years, loss due to disease remained as a major problem. Vibriosis caused by Vibrio harveyi, V.anguillarium V.alginolyticus is one of the major concern in shellfish aquaculture. Administration of probiotics is an effective alternative to the use of chemicals and antibiotics for the prevention of pathogens. Probiotics are the live microorganisms which are known for their ability to improve growth, water quality and immune responses of cultured species. Bacillus, Lactobacillus sps are commonly used as probiotics in shrimp aquaculture as supplementation along with feed or directly inoculated into rearing systems. The peculiar feeding characteristics of brine shrimp, Artemiafranciscana enabled its use for delivering vaccines. Hence, the present study is carried out to understand the influence of bioencapsulated Bacillus, Lactobacillus Artemianauplii in the enhancement of digestive enzymes in Peneaus monodon. Amplification of B.subtilis by 83%, 99.5% and 107% and L.sporogenes by 52%, 64.5% and 86% administered to 2ndinstarartemianauplii secured following 3, 5 and 8hrs of feeding respectively indicating this potential use as bio encapsulating agent. Increase in B.subtilis to 392 and 432 CFU/ml and L.sporogenesto 300 and 356CFU/after Day1 and Day 2 respectively further ensured their colonization in the host. Feeding of encapsulated B.subtilisup to 60 days resulted in 61, 46 and 76% increase in the activity of amylase, protease and lipase respectively while encapsulated L.sporogenes diet resulted in 35,17and 63% increase in the same. Hence, this study clearly showed the ensured delivery of gut probiotics through bioencapsulation to obtain the anticipated benefit.